2014
DOI: 10.4236/health.2014.615234
|View full text |Cite
|
Sign up to set email alerts
|

State Scholarship and Loan Forgiveness Programs in the United States: Forgotten Driver of Access to Health Care in Underserved Areas

Abstract: State-supported programs providing loans and scholarships in exchange for service in underserved areas provide an important source of financial support for medical students while encouraging them to select careers in primary care. The purpose of this research was to seek a better understanding of these often unheralded but important state sources of support, and learn if they have continued to grow in the twenty-first century. Administrative data were obtained on statesupported programs operating in 2008 that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…For instance, loan forgiveness programs and scholarships targeted toward providers practicing in underserved communities could improve the primary care and behavioral health workforce in underserved areas. 50 National Health Service Corps scholarships and loan repayment programs 51 in addition to Minority Fellowship Programs funded through the Substance Abuse and Mental Health Services Administration 52 explicitly place primary care and behavioral health professionals in underserved health professional shortage areas. Payment reform policies could support the provision of integrated primary care clinics that provide collaborative, team-based, same-day primary care services and behavioral health services in shared clinical space.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, loan forgiveness programs and scholarships targeted toward providers practicing in underserved communities could improve the primary care and behavioral health workforce in underserved areas. 50 National Health Service Corps scholarships and loan repayment programs 51 in addition to Minority Fellowship Programs funded through the Substance Abuse and Mental Health Services Administration 52 explicitly place primary care and behavioral health professionals in underserved health professional shortage areas. Payment reform policies could support the provision of integrated primary care clinics that provide collaborative, team-based, same-day primary care services and behavioral health services in shared clinical space.…”
Section: Discussionmentioning
confidence: 99%
“…3 Numerous studies documented and assessed the effects of such programs. In 2008, 75 state programs operating across 37 states had more than 5,000 health providers under contract, including 492 newly contracted physicians (Geletko et al, 2014). In their systematic literature review on primary care physicians’ location choice predictors, Goodfellow et al (2016) found that financial incentives were among the most important underlying factors influencing primary care physicians.…”
Section: Literature Reviewmentioning
confidence: 99%
“…11 Overall, the percentage of dentists practicing in rural communities was low compared with the level of the state’s rurality status, for example, only 3% of the dentists practiced in rural communities in Georgia, and 40% of the state is considered rural. 11 This finding suggests that the supply of dental care for children was insufficient in rural communities during the study period; interventions such as loan forgiveness programs 12 , 13 or school-based mobile care may help address such shortages. 14 , 15 , 16…”
Section: Discussionmentioning
confidence: 99%